Extracting female inbred lines from commercial sunflower hybrids - Carvalho, Claudio Guilherme Portela de; Toledo, José Franscisco Ferraz de (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this study was to obtain female inbred lines from sunflower (Helianthus annuus) hybrids. A methodology based on altering inbred lines carrying the fertility restorer gene (Rf) obtained from self pollinating hybrids into inbred lines with normal cytoplasm without the Rf gene was described. Further, derived male-sterile inbred lines were developed. The methodology was successfully used to obtain female inbreds from sunflower commercial hybrids. Although more time and labor consuming than the conventional female inbred line extraction methods, this methodology is advantageous in exploiting superior germplasms (commercial hybrids), which prompted us to develop practical procedures to allow its routinely use.